2012
DOI: 10.1038/ng.2343
|View full text |Cite
|
Sign up to set email alerts
|

The yak genome and adaptation to life at high altitude

Abstract: Domestic yaks (Bos grunniens) provide meat and other necessities for Tibetans living at high altitude on the Qinghai-Tibetan Plateau and in adjacent regions. Comparison between yak and the closely related low-altitude cattle (Bos taurus) is informative in studying animal adaptation to high altitude. Here, we present the draft genome sequence of a female domestic yak generated using Illumina-based technology at 65-fold coverage. Genomic comparisons between yak and cattle identify an expansion in yak of gene fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
737
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 769 publications
(767 citation statements)
references
References 66 publications
23
737
5
2
Order By: Relevance
“…5b). relatives (Qiu et al 2012;Cai et al 2013). With regard to ADAM9, previous study has showed that the mRNA and protein expression levels of this gene are elevated by the 14 regulation of reactive oxygen species under hypoxic stress conditions in prostate cancer cells (Shen et al 2013).…”
Section: Signatures Of Deleterious Variation and Positive Selectionmentioning
confidence: 99%
“…5b). relatives (Qiu et al 2012;Cai et al 2013). With regard to ADAM9, previous study has showed that the mRNA and protein expression levels of this gene are elevated by the 14 regulation of reactive oxygen species under hypoxic stress conditions in prostate cancer cells (Shen et al 2013).…”
Section: Signatures Of Deleterious Variation and Positive Selectionmentioning
confidence: 99%
“…Positively selected and rapidly evolving genes in the yak lineage are also found to be significantly enriched in functional categories and pathways related to hypoxia and nutrition metabolism. These findings may have important implications for understanding adaptation to higher altitudes in other animal species and for hypoxia-related diseases in humans (Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 84%
“…Using either experimentally determined gene/protein function or sequence similarity to previously identified functions, the activities of individual genes are paired with specific numeric codes. Gene Ontology analyses have been used in other studies to determine the functional components to a variety of traits, adaptations and physiologies of interest, including adaptation to high altitudes (Qiu et al, 2012), depth tolerance in deep-sea bacteria (Vezzi et al, 2005), and a number of human disorders (Ahn et al, 2003;Holmans et al, 2009); however, these have identified known genes of interest and then drawn conclusions of function popt hoc. Rather than assigning the Gene Ontology codes first and subsequently determining the functions of particular interest as has been done previously, we can select functions of expected relevance a priori in order to allow for quantitative testing of their adaptive relevance by comparing functions in genomes in species that exhibit a convergent function.…”
Section: Intnoductionmentioning
confidence: 99%